1. ## urgent help needed

can anyone help with this

i have r = [ 1 - (1 - 1/Tr)^L]

and i need to make Tr the subject urgently if someone could show me that would be great

2. Originally Posted by question
can anyone help with this

i have r = [ 1 - (1 - 1/Tr)^L]

and i need to make Tr the subject urgently if someone could show me that would be great
$\displaystyle r = 1 - (1 - 1/Tr)^L$

$\displaystyle r - 1 = - (1 - 1/Tr)^L$

$\displaystyle 1 - r = (1 - 1/Tr)^L$

$\displaystyle log_L (1 - r) = 1 - 1/Tr$

$\displaystyle 1/Tr = 1 - log_L (1 - r)$

$\displaystyle Tr = \frac{1}{1 - log_L (1 - r)}$

-Dan

3. ## need help

thanks the log to the base L also confuses me how exactly does it go into the calculator or is there another way of calculating it

4. Originally Posted by topsquark
$\displaystyle r = 1 - (1 - 1/Tr)^L$

$\displaystyle r - 1 = - (1 - 1/Tr)^L$

$\displaystyle 1 - r = (1 - 1/Tr)^L$

$\displaystyle log_L (1 - r) = 1 - 1/Tr$

$\displaystyle 1/Tr = 1 - log_L (1 - r)$

$\displaystyle Tr = \frac{1}{1 - log_L (1 - r)}$

-Dan
does anyone know how to put the base log into a calculator or any other way of doing it?????